Pengobatan Suportif Vitamin D Mempercepat Konversi Sputum dan Perbaikan Gambaran Radiologis Penderita T uberkulosis - Siswanto, Siswanto; Sumarno, Sumarno; Jane, Yani; Widayanti, Oeryana Agustin; Muktiati, Nunuk Sri (Fakultas Kedokteran Universitas Brawijaya, 2009)
Pulmonary T uberculosis remains as a major health problem in South East Asia as well as Indonesia. The failure of tuberculosis treatment is mostly due to drop-out and multiple drugs resistant. Previous study showed that Vitamin D increase the intracellular cathelicidin which has potency to kill the Mycobacterium tuberculosis. This research was aimed to identify the effect of Vitamin D as supportive treatment on the improvement of sputum conversion, radiographic finding and TNF-α serum concentration. A Double-blind randomized control trial was used in two random allocated patient group with standard tuberculosis treatment. The first group was treated with Vitamin D (800 iu/day) while the other was not. Subjects were evaluated using three parameters i.e. sputum conversion, radiographic finding and TNF-α serum concentration. Compared to the group without vitamin D supplementation, group with vitamin D has higher proportion of sputum conversion in the first month (67% vs. 34%, p=0,04) and second month (95% vs. 77%, p=0,18). Improvement in radiographic findings in the group with vitamin D is also higher in the first month (67% vs. 18%, p=0,02) and second month (76% vs. 45%, p=0,06). There is a significant difference in the level of 25-dihidroxyvitamin D between two groups (p=0,00). However, there is no significant difference in the level of TNF-α between two groups (p=0,76) after two months.